(untitled) - Baker, Ann (Cambridge (New York), 2014)
This is a revised and updated edition of the classic pronunciation title Ship or Sheep? This new edition of Ship or Sheep?, an accessible intermediate-level pronunciation course in full colour for students of English, provides systematic practice of English pronunciation, with an emphasis on minimal pairs, through a wide variety of interesting exercises and activities.
Keywords: English language,English language,English language,Tiếng Anh; Pronunciation,Spoken English,Phát âm